A framework for identifying and learning from countries that demonstrated exemplary performance in improving health outcomes and systems. Issue 12 (3rd December 2020) - Carter, Austin; Akseer, Nadia; Ho, Kevin; Rothschild, Oliver; Bose, Niranjan; Binagwaho, Agnes; Hirschhorn, Lisa R; Price, Matthew; Muther, Kyle; Panjabi, Raj; Freeman, Matthew C; Bednarczyk, Robert A; et al.
Abstract : This paper introduces a framework for conducting and disseminating mixed methods research on positive outlier countries that successfully improved their health outcomes and systems. We provide guidance on identifying exemplar countries, assembling multidisciplinary teams, collecting and synthesising pre-existing evidence, undertaking qualitative and quantitative analyses, and preparing dissemination products for various target audiences. Through a range of ongoing research studies, we illustrate application of each step of the framework while highlighting key considerations and lessons learnt. We hope uptake of this comprehensive framework by diverse stakeholders will increase the availability and utilisation of rigorous and comparable insights from global health success stories.